2019
DOI: 10.3390/ijms20153777
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Application Enhances Drought Stress Tolerance in Sugar Beet and Promotes Plant Biomass and Beetroot Sucrose Concentration

Abstract: Numerous studies have demonstrated the potential of sugar beet to lose the final sugar yield under water limiting regime. Ample evidences have revealed the important role of mineral nutrition in increasing plant tolerance to abiotic stresses. Despite the vital role of calcium (Ca2+) in plant growth and development, as well as in stress responses as an intracellular messenger, its role in alleviating drought stress in sugar beet has been rarely addressed. Here, an attempt was undertaken to investigate whether, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 82 publications
3
37
0
2
Order By: Relevance
“…The biosynthesis of ABA has improved water use efficiency and confer drought tolerance in plants [28]. Calcium foliar application improved drought tolerance in maize [29], sugar beet [30], wheat [31], and tea [32]. Fan [33] indicated that Ca concentration of 10 mM achieves the highest maize grain yield under both normal and drought conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The biosynthesis of ABA has improved water use efficiency and confer drought tolerance in plants [28]. Calcium foliar application improved drought tolerance in maize [29], sugar beet [30], wheat [31], and tea [32]. Fan [33] indicated that Ca concentration of 10 mM achieves the highest maize grain yield under both normal and drought conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Salinity reduces plant growth, creates an imbalance in soilwater, disrupts plant cell functions and induces metabolic disorders in plants. Nanoparticles such as nitric oxide are reportedly efficient in reducing salinity, and similarly, Ca is known to regulate the salinity of soil [3,40,[58][59][60]. Correspondingly, CaNPs would be efficiently better as a soil conditioner to reduce salinity stress and provide essential minerals by maintaining K concentration.…”
Section: Discussionmentioning
confidence: 99%
“…This could be resulted from the high calcium content of the applied soil amendments which is antagonized with sodium ions and improves soil aggregation and hence improves the chemical and physical soil characteristics and ultimately enhances plant growth and yield (Miller &Smith 2010). Moreover, the high sucrose content resulted from the control treatment might be due to that the partitioning of photoassimilates was in favor of increasing sucrose content in the control treatment where root yield was decreased (Hosseini et al 2019, Koch et al 2019, Lemoine et al 2013, Sowiński 1999). In addition, sucrose content has been reported to be reduced in response to increasing beet root yield by the dilution effect (Shaheen et al 2017).…”
Section: Application Of Treated Lter Cake and Molasses Enhances Soil Chemical Propertiesmentioning
confidence: 99%